Preadaptative Transactions and Institutional Change: Wolf-critical activism in southwestern Finland - Hiedanpää, Juha; Pellikka, Jani
Finland has had problems protecting the grey wolf (Canis lupus) for decades. Over the past few years, the government of Finland has taken several steps to improve its policy on wolves. In this paper, we explore the grassroots activism that institutional adjustments have triggered. This work builds on ethnographic presence in two southwestern Finnish wolf territories. Theoretically, we draw from institutional theory and use transactions as the unit of analysis. We identify four ways in which wolf-critical civil society has provided an institutional basis for particular changes: (i) questioning the purity of the wolf, (ii) making scientific evidence fallible, (iii) producing negative emotional effects and (iv) maintaining strong policy pressure against the presence of the wolf. In the discussion, we explain how these modifications have functioned. Actors critical of the wolf have exercised the politics of disturbance, produced various epistemic cues and created conditions for reframing existing rights and the emergence of new ones. Due to these bottom-up preadaptive transactions, wolf-policy-related institutional adjustments have, in many respects, taken on volitional and spontaneous features. 2017